Mendelian randomization study of maternal influences on birthweight and future cardiometabolic risk in the HUNT cohort - Gunn-Helen Moen (Nature Portfolio, 2020)
Observationally, lower birthweight is a risk factor for cardiometabolic disease. Using Mendelian Randomization, the authors investigate whether maternal genetic factors that lower offspring birthweight also increase offspring cardiometabolic risk and show that the observational correlation is unlikely to be due to the intrauterine environment.